Assessment of WWW-Based Ranking Systems for Smaller Web Sites - Ågren, Ola (INFOCOMP Journal of Computer Science, 2006)
A comparison between a number of search engines from three different families (HITS, Page- Rank, and Propagation of Trust) is presented for a small web server with respect to perceived relevance. A total of 307 individual tests have been done and the results from these were disseminated to the algorithms, and then handled using confidence intervals, Kolmogorov-Smirnov and ANOVA. We show that the results can be grouped according to algorithm family, and also that the algorithms (or at least families) can be partially ordered in order of relevance.